KEWAJIBAN PENCATATAN KELAHIRAN OLEH ORANG TUA ASUH ATAS ANAK YANG TIDAK DIKETAHUI ASAL USULNYA DI KELURAHAN ROBAN KECAMATAN SINGKAWANG TENGAH KOTA SINGKAWANG - NIM. A1011151065, RESTU MAHHENDRA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac This thesis is the result of field research with the title Obligation of Birth Registration by Foster Parents for Children of Unknown Origin in Roban Village, Singkawang Tengah District, Singkawang City. Until now, there are still many Indonesian children whose identities are not/not yet recorded in birth certificates, de jure their existence is considered non-existent by the state. As a result, the child born is not registered with his name, genealogy and nationality and his existence is not protected. Many problems that occur stem from manipulation (engineering) of children's identities, the more unclear the identity of a child, the easier it is for exploitation of children such as children becoming victims of trafficking in infants and children, labor and violence.The formulation of the problem in this study is